The antibacterial activity of diluted "tualang" honey - Nurdiyana' Aqilah Roslan (2013)
The present study is to determine the antibacterial activity of diluted honey against Escherichia coli (E. coil). Limited information is available on the antibacterial mechanism of local honey. This study was carried out in order to determine the antibacterial activity of local honey, "Tualang" against E. coli. Three different honey concentrations; 20%, 30% and 40% were used to observe effect of diluting honey on its antibacterial effect towards E. co/i. The 40% diluted honey was the most effective in inhibiting the growth of E. coli, was followed by honey diluted at 20% and 30%. The higher antibacterial activity of honey towards E. coli was probably due to the higher honey concentration.